Roads Tell Stories - Ramos, M. (Coloquium of the 25th World Day of Remembrance of Road Traffic Victims, 18 November, Conservatorio de Música de Barcelona, Barcelona, 2018)
The streets and roads tell stories. This was the theme chosen by the European Federation of Road Traffic Victims (FEVR) to mark the celebrations of World Day of Remembrance for Road Victims, in its twenty-fifth anniversary. And how many stories do they tell? Thousands, millions of stories. The point is: what stories are told and what stories we prefer to hear. Roads have stories of all kinds: comic, cheerful, boring, dramatic and unfortunately also tragic. Of tragic stories, those that do not end well, that end in suffering, pain and loss, we know that there are many, and that each of us may become (or has already became) the involuntary protagonist in one of them. What do they say, why they are told, how are they told, the road stories that do not end well? Who wants to hear them, and when?